Efficiency evaluation of major container terminals in the top three cities of the Pearl River Delta using SBM-DEA and undesirable DEA - Siwei Liu; Sung-Hoon Park; Young-Seo Choi; Gi-Tae Yeo (Asian Journal of Shipping and Logistics (AJSL), 2022)
As the three largest central hub cities in the Pearl River Delta (PRD) region, Hong Kong, Guangzhou, and Shenzhen have played critical roles in regional growth. Nevertheless, these ports face many challenges, such as port handling capacity, environmental problems, and the expansion of the complex transportation system owing to the large volume of goods. Therefore, this study used the slacks-based measure-data envelopment analysis (SBM-DEA) and DEA-undesirable models to evaluate the efficiency of the major container terminals in these three cities between 2018 and 2019. Based on the decision-making unit values of the terminals for the past two years, Yantian and Container Terminal 9 (South) were the most efficient, followed by container terminals 6 and 7. Moreover, the efficiency of the major container terminals in Guangzhou was less satisfactory than that of terminals in Shenzhen and Hong Kong. The results provide a reliable reference for future port investment, and regional development policy in the PRD region.
Keywords: 650; Container terminal; Efficiency evaluation; Pearl river delta; SBM-DEA model; Undesirable DEA